Regulation and the future of work: The employment relationship as an innovation facilitator - Aloisi, Antonio; De Stefano, Valerio (Wiley, 2020)
Digital transformation and the reorganization of the firm have given rise to new forms of work that diverge significantly from the standard employment relationship. Advocates of digital disruption suggest that the existing legal framework cannot accommodate “innovative” working templates and business models. This article, however, argues that labour regulation can continue to facilitate innovation, presenting the employment relationship as a flexible instrument, and standard forms of employment as the means of achieving efficiencies and cost advantages. First, they allow for the full exercise of managerial prerogative and attendant internal flexibility in workforce deployment, and, second, they constitute an effective device to deliver training and develop skills.
Keywords: Regulation; 56 Ciencias Jurídicas y Derecho; ODS 4 - Educación de calidad; ODS 8 - Trabajo decente y crecimiento económico